An analgesic to bridge the gap between Narcotics and NSAIDs: opiorphin - S., Sujatha; R., Priyadharshini; Nejad, Niloofar Khansari; B. K., Yashoda Devi; V., Shwetha; T., Pavan Kumar; Azmi, Rizwana (International Journal of Basic & Clinical Pharmacology, 2018)
Pain management is an all-time challenge in dentistry. Discontent to pain management is a concern among patients and professionals. Unrelieved pain affects physical and mental well-being contributing to delayed recovery, psychological distress and anxiety. Studies have revealed that chronic pain interferes with normal daily chores of the individual like exercise, sleep, social life and lifestyle. At one end of pain management spectrum are Non-steroidal anti-inflammatory drugs (NSAIDs) while at the other end are the opioids. These drugs are not without constituent side effects. The quest is for new analgesics with potent and long term analgesia with minimal or no side effects. An analgesic that is intermediate in this spectrum is the need of the hour. Opiorphin is an endogenous peptide isolated from human saliva. Opiorphin produces analgesia, by inhibiting enkephalin (ENK) metabolizing enzymes, thus increasing the half-life of circulating ENKs. Apart from being a potent analgesic it can also be a potential biomarker for various systemic and psychosocial disorders. This review focuses on the pharmacological effects of opiorphin and its potential role as a biomarker in various disease conditions.